OFF-LABEL PEDIATRIC DRUG USE IN INDONESIA : A SYSTEMATIC REVIEW - Dewi Latifatul Ilma; Nialiana Endah Endriastuti (Jurnal Farmasi Sains dan Praktis, 2020)
The phenomenon of off-label drug use has been widely observed in the pediatric population, including in Indonesia. The major concern arising from the prevalence of off-label drug use is the increased risk of adverse drug reactions. We performed a systematic review to describe and provide insight into off-label pediatric drug use in Indonesia. The articles published using English and Indonesian language was systematically searched in five electronic databases, including Pubmed, Scopus, Google Scholar, Garuda, and Neliti. Key terms used for the search were as follows: "off-label use", "off-label”,"child", "pediatrics", "infant","adolescent", "newborn", "Indonesia". A total of one hundred sixteen studies were initially obtained from an electronic database. Further, after the references were reviewed, ten articles met all the eligibility criteria that were finally selected. The percentage of off-label pediatric drug use was 32.6-89.9%. The off-label categories in the selected studies were age, dosage, contraindication, route of administration, and indication. Among these off-label categories, age was the highest off-label with percentages ranged from 19.8 to 92.9%. Pseudoephedrine hydrochloride and triamcinolone acetonide became the most frequently used drug in that category. Thus we conclude that off-label pediatric drug use is common in Indonesia. Future research should consider the safety of off-label drugs in pediatric, primarily in Indonesia. Clinicians should be aware of off-label drugs in pediatrics and consider the risk-benefit of the drugs when prescribing to children. The authorities need to regulate off-label drug prescribing in pediatrics; therefore, it could improve medication safety and quality.